2015
DOI: 10.1039/c4nr05737f
|View full text |Cite
|
Sign up to set email alerts
|

Laser-ablation production of graphene oxide nanostructures: from ribbons to quantum dots

Abstract: A new one-step method for the preparation of graphene oxide (GO) nanostructures has been developed by pulsed laser ablation in GO solution. The formation of different shapes of GO nanostructures, such as ribbons, nanoflakes (including nano-squares, nano-rectangles, nano-triangles, nano-hexagons, and nano-disks) and quantum dots, has been demonstrated by scanning electron microscopy and transmission electron microscopy. Photoreduction for the GO occurred during irradiation by the pulsed laser. The GO quantum do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 39 publications
1
52
0
Order By: Relevance
“…Rashid et al [31] reported the synthesis of GOQDs from graphite nanofibers with good photoluminescence properties. Lin et al [32] produced blue photoluminescence GOQDs by laser-ablation. However, all these reported methods are time consuming and therefore, it is important to develop an entirely new approach to synthesis GOQDs with good optical properties in shorter reaction time.…”
Section: Introductionmentioning
confidence: 99%
“…Rashid et al [31] reported the synthesis of GOQDs from graphite nanofibers with good photoluminescence properties. Lin et al [32] produced blue photoluminescence GOQDs by laser-ablation. However, all these reported methods are time consuming and therefore, it is important to develop an entirely new approach to synthesis GOQDs with good optical properties in shorter reaction time.…”
Section: Introductionmentioning
confidence: 99%
“…Typically,g raphene-related nanomaterials have been synthesized by ablatinghighly oriented pyrolytic graphite (HOPG) in water. [17,18] Fortunately,B Prelatedn anomaterials can also be prepared by meanso fthe PLA method.…”
Section: Introductionmentioning
confidence: 99%
“…22 A 1064 nm LASER was able to ablate the surface of a graphite plate immersed in liquid via thermal relaxation process. 23,24 Ablation of graphite plate resulted in the formation of large sheets of graphene layers (single and multiwall) and GQDs in solution (see Fig. S2 †).…”
Section: Resultsmentioning
confidence: 99%